Lactate and ventilatory thresholds reflect the training status of professional soccer players where maximum aerobic power is unchanged - Edwards, A. M.; Clark, N.; Macfadyen, A. M. (Journal of Sports Science & Medicine, 2003)
The aim of this study was to investigate maximum aerobic power (VO2 max) and anaerobic threshold (AT) as determinants of training status among professional soccer players. Twelve professional 1st team British male soccer players (age: 26.2 ± 3.3 years, height: 1.77 ± 0.05 m, body mass: 79.3 ± 9.4 kg) agreed to participate in the study and provided informed consent. All subjects completed a combined test of anaerobic threshold (AT) and maximum aerobic power on two occasions: Test 1) following 5 weeks of low level activity at the end of the off-season and Test 2) immediately following conclusion of the competitive season. AT was assessed as both lactate threshold (LT) and ventilatory threshold (VT). There was no change in VO2 max between Test 1 and Test 2 (63.3 ± 5.8 ml·kg-1·min-1 vs. 62.1 ± 4.9 ml·kg-1·min-1 respectively), however, the duration of exercise tolerance (ET) at VO2 max was significantly extended from Test 1 to Test 2 (204 ± 54 vs. 228 ± 68 s respectively) (P<0.01). LT oxygen consumption was significantly improved in Test 2 versus Test 1 (P<0.01) VT was also improved (P<0.05). There was no significant difference in VO2 (ml·kg-1·min-1) corresponding to LT and VT. The results of this study show that VO2 max is a less sensitive indicator to changes in training status in professional soccer players than either LT or VT.